Claudin-1 Mediated Tight Junction Dysfunction as a Contributor to Atopic March - Xia, Yuhan; Cao, Han; Zheng, Jie; Chen, Lihong (Frontiers in Immunology, 2022)
Atopic march refers to the phenomenon wherein the occurrence of asthma and food allergy tends to increase after atopic dermatitis. The mechanism underlying the progression of allergic inflammation from the skin to the gastrointestinal tract and airways, remains unclear. Impaired skin barrier is proposed as a risk factor for allergic sensitization. Claudin-1 protein forms tight junctions and is highly expressed in the epithelium of the skin, lungs and gastrointestinal tract, thus, the downregulation of claudin-1 caused by CLDN-1 gene polymorphism can mediate common dysregulation of epithelial barrier function in these organs, potentially leading to allergic sensitization at various sites. Indeed, in patients with atopic dermatitis, asthma and food allergy, claudin-1 expression level was significantly downregulated in the skin, bronchial and gut epithelium respectively. Knockdown of claudin-1 in mouse models of atopic dermatitis and allergic asthma exacerbated allergic inflammation, proving that claudin-1 downregulation contributes to the pathogenesis of allergic diseases. Therefore, we propose the hypothesis that: the tight junction dysfunction mediated by claudin-1 downregulation contributes to atopic march. Further validation with clinical data from patients with atopic march or mouse models of atopic march is needed. If this hypothesis is tested to be true, impaired claudin-1 expression will be a risk factor and likely a diagnostic marker for atopic march. Claudin-1 may serve as an attractive target to slowdown or block the progress of atopic march.